HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN SMASH BOLA VOLI PUTRI TIM MUTIARA KABUPATEN SLEMAN YOGYAKARTA - Fahrul Rifqi; Ardhika Falaaahudin (Yayasan Nusantara Hasana Berdikari, 2023)
The research uses a quantitative type of research with correlational research methods. The population used is the Mutiara Volleyball Womens Team, Sleman Yogyakarta Regency, totaling 20 players with a total sampling technique. The instruments used in the research were the vertical jump dan push-up tests, namely the vertical jump test to measure the explosive power of the leg muscles, while the push-up measured the strength of the armmuscles. Data analysis used the product moment correlation technique and continued with multiple correlation. The results of this study show: (1) there is a relationship between leg muscle explosive power and volleyball smash ability in the Mutiara Women’s Volleyball Team, Sleman Regency, Yogyakarta, found with a value of r count > r table, namely 0,645 > 0,444, while t count (4,306) > t table (2,101). (2) there is a relationship between arm muscle strength and volleyball smash ability in the Mutiara Volleyball Women’s Team, Sleman Regency, Yogyakarta, found with a value of r count > r table, namely 0,644, while t count (4,299) > t table (2,101). (3) there is a relationship between the explosive power of the leg muscles and the strength of the arm muscles on the volleyball smash ability of the Mutiara Volleyball Women’s Team, Sleman Regency, Yogyakarta. And arm muscle strength, with smash ability, with f count (21,89) > f table (3,55). In conclusion, there is a relationship between leg muscle explosive power and arm muscle strength on the smash ability of the Mutiara Women’s Volleyball Team, Sleman Regency, Yogyakarta.